Simulation Development of Ultra Capacitor Bank in Energy Management Strategies through Regenerative Braking in Diesel Locomotive - Adarsh Jitendra Mehta,; Amruta Ankush Gaikwad - Patil, (International Journal of Innovations in Engineering Research and Technology, 2021)
The aim of this paper to build a ultra-capacitor(UC) bank, dc to dc converter topology , and testing rig to perform efficiency testing for various configurations for dc drive with dc motor with the super capacitor bank against various hybrid electric vehicle regenerative braking profiles. A bank of 5F cells was constructed along with a bidirectional DC to DC converter or achopper allowing practical testing in two of the four possible bank configurations.